2022
DOI: 10.3390/land11081209
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Relationship between Industrial Land Expansion and Economic Development in China

Abstract: Economic expansion has caused increasingly serious land resource problems, and the decoupling of urban industrial land expansion from economic development has become a big topic for intensive development. The current research has mainly concerned industrial land efficiency, a single, static indicator, compared to a decoupling model, which takes into account two variables and gives a full expression of the spatio-temporal dynamic characteristics. However, little attention has been paid to the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…This was accomplished by directly generating highresolution (30 m) IND areas for ten countries, utilizing a combination of satellite-based multiple datasets and machine learning techniques. Previous research has relied on national statistical data or pointsource-based data 12,14,17 , inherently limited their scope to highly localized areas, such as individual countries. This study, by contrast, constructed spatially continuous IND areas at a high resolution, allowing us to trace IND distribution and its expansion over two decades across 216 subnational regions in ten countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was accomplished by directly generating highresolution (30 m) IND areas for ten countries, utilizing a combination of satellite-based multiple datasets and machine learning techniques. Previous research has relied on national statistical data or pointsource-based data 12,14,17 , inherently limited their scope to highly localized areas, such as individual countries. This study, by contrast, constructed spatially continuous IND areas at a high resolution, allowing us to trace IND distribution and its expansion over two decades across 216 subnational regions in ten countries.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies focusing on China have demonstrated that industrial land expansion has a positive interaction with economic growth 4,11,12 and is a major influencing factor in CO 2 emissions [13][14][15][16] . Regional case studies suggest that the impact of industrial land on economic growth and CO 2 emissions may differ in regions depending on socioeconomic achievements 17,18 . However, there is little understanding of how these impacts differ across multiple countries with varying levels of development over time.…”
mentioning
confidence: 99%
“…The elastic decoupling theory is a theory used to quantitatively determine the relationship between the fitness of different variables on time series, and Tapio developed its refinement to form the Tapio decoupling model [49]. This model can be used to judge the degree of decoupling between different objects at different scales and is widely used in research on carbon emissions [50], resource consumption [51], industrial development [52], energy utilization [50], and other related fields of resources and environment. This study defines the harmonious relationship between energy utilization efficiency and industrial structure development as a dynamic coordination and balance relationship on a time scale which can reflect the dynamic adaptation state of the two in the development process.…”
Section: Tapio Decoupling Modelmentioning
confidence: 99%
“…A strong relationship depends on the value the client and seller share (Konhäuser, 2008). Most industries focus on this perspective where both parties collaborate in a transparent environment and share their knowledge and information to get shared value and mutual benefits (Qi, Hu, Han, Zheng, & Wang, 2022). Based on existing literature support, it is hypothesized that H1: Relational benefits significantly impact customer satisfaction in B2B marketplace Switching Barrier as a Mediator between Relational Benefits and Customer Satisfaction Jones, Mothersbaugh, and Beatty (2000) found that socially based switching barriers can be created when clients are scared of losing personal relationships established by service providers; by putting in some resources and effort, companies can build a strong relationship with their customers that is not quickly competed by competitors (Peltier & Westfall, 2000).…”
Section: Relational Benefits and Customer Satisfactionmentioning
confidence: 99%